2013
DOI: 10.3329/bccj.v1i1.14368
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of 1255 ICU Patients at a Tertiary Military Hospital

Abstract: An intensive care unit (ICU) is a special part of hospital where expertise medical and nursing care has been provided along with monitoring and organ support. An analysis of 1255 patients was carried out to investigate retrospective review of data from ICU of combined military hospital (CMH) Dhaka. During this study period, the frequency of admission into ICU was more from medical discipline (59.92%) than other disciplines like surgical (37.52%), gynaecological, obstetric and other disciplines (2.55%). The inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
2
1
1
Order By: Relevance
“…In TUTH ICU, the best outcome was found in patients following elective surgeries amongst which also neurosurgical patients had the best outcomes. The outcomes of the surgical patients were better than the medical patients and our are similar to the study done by Vaidya PR et al 3 and MHM Delwar H et al 10 Patients admitted primarily for renal problems had the worst outcome followed by patients with respiratory illnesses.…”
Section: Discussionsupporting
confidence: 89%
“…In TUTH ICU, the best outcome was found in patients following elective surgeries amongst which also neurosurgical patients had the best outcomes. The outcomes of the surgical patients were better than the medical patients and our are similar to the study done by Vaidya PR et al 3 and MHM Delwar H et al 10 Patients admitted primarily for renal problems had the worst outcome followed by patients with respiratory illnesses.…”
Section: Discussionsupporting
confidence: 89%
“…It was significantly higher among the patients from surgery discipline (p<0.001). The finding is different from the findings of Hossain et al 15 where it was found that requirement of ventilatory support is much less than that of other ICUs (45.34%)…”
Section: Discussioncontrasting
confidence: 98%
“…In our study, medicine specialty is observed to be the highest specialty utilizing the ICU bed spaces in last 5 years, 1035 (55.20%). Findings are similar with the profile of another tertiary hospital of Chittagong, Chittagong Military Hospital (CMH) where the prevalence of admission into this ICU was more from medical discipline (59.92%) than that of other disciplines like surgical (37.52%) discipline 15 . This was different from the study done by Abubakar et al 16 where there were a total of 114 admissions into their critical care unit in one year and they were majorly surgical patients (66.7%).…”
Section: Discussionsupporting
confidence: 79%
“…length of stay and organizational aspects of the unit and corresponding mortality in the hospitalized patients was 30 to 42.2% 10,11,12 . A study done in CMH Dhaka, it was found that the incidence of mortality was more in medical discipline (46.14%) than surgical discipline (31%) and least in gynaecological and other disciplines (15.62%) and total ICU mortality rate was 39.69% 13 .Another study done in ICU Bangabandhu Sheikh Mujib Medical University, Dhaka from January 2006 to December 2006 Overall mortality of ICU admitted patient were 60.61% 14 . In our study, it was found that the incidence of mortality was more in gynaecological and other disciplines (61.53%) than medical discipline (55.76%%) and least in surgical discipline (43.35%) and total ICU mortality rate was 51%, which is comparable to other ICUs ( Table -II…”
Section: Discussionmentioning
confidence: 97%